2006
DOI: 10.1038/nature04543
|View full text |Cite|
|
Sign up to set email alerts
|

The prolyl isomerase Pin1 regulates amyloid precursor protein processing and amyloid-β production

Abstract: Neuropathological hallmarks of Alzheimer's disease are neurofibrillary tangles composed of tau and neuritic plaques comprising amyloid-beta peptides (Abeta) derived from amyloid precursor protein (APP), but their exact relationship remains elusive. Phosphorylation of tau and APP on certain serine or threonine residues preceding proline affects tangle formation and Abeta production in vitro. Phosphorylated Ser/Thr-Pro motifs in peptides can exist in cis or trans conformations, the conversion of which is catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
513
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 456 publications
(530 citation statements)
references
References 28 publications
12
513
3
2
Order By: Relevance
“…The ratios of cross to diagonal peak intensities for cis and trans conformations in the ROESY spectra were dependent on the total exchange rate constant k ex of a two-state exchange process (cis2trans) and the mixing time of the ROESY experiments (t m ). The exchange rate constants were obtained by fitting one of the following equations using different ratios with different mixing times 59,60 :…”
Section: Methodsmentioning
confidence: 99%
“…The ratios of cross to diagonal peak intensities for cis and trans conformations in the ROESY spectra were dependent on the total exchange rate constant k ex of a two-state exchange process (cis2trans) and the mixing time of the ROESY experiments (t m ). The exchange rate constants were obtained by fitting one of the following equations using different ratios with different mixing times 59,60 :…”
Section: Methodsmentioning
confidence: 99%
“…A recent work provided a possible link between Thr 668 phosphorylation and APP processing through the prolyl isomerase Pin1. The authors showed that Pin1 binds to the phosphorylated Thr 668 -Pro motif and promotes the isomerization of the proline residue (85). This leads to a conformational change of the APP intracellular domain and alteration of APP processing and Aβ production.…”
Section: Putative Functions Of Appmentioning
confidence: 99%
“…Proline cis-trans isomerization has emerged as a particularly efficient regulatory mechanism in many biological processes, including cell signaling, [62][63][64][65] neurodegeneration, 66 amyloidogenesis, 67 channel gating, 68 gene regulation, 69,70 phage and virus infection, 71,72 enzyme function, 73,74 and ligand recognition. 75 Proline isomerization is unique in that it exerts its function through multiple mechanisms involving (i) significant conformational changes caused by the 180 rotation about the prolyl bond, (ii) slow kinetics of isomerization affording a molecular timer, and (iii) the recruitment of prolyl cis-trans isomerase enzymes (PPIases).…”
Section: Protein Activity Regulation By a Proline Switchmentioning
confidence: 99%